2019
DOI: 10.1093/ejcts/ezz180
|View full text |Cite
|
Sign up to set email alerts
|

Left thoracotomy approach for off-pump coronary artery bypass grafting surgery: 15 years of experience in 2500 consecutive patients

Abstract: • Reproducible surgery • Low mortality and early complications rate • Good early, mid and long-term results Take-home message The left thoracotomy is a safe alternative to median sternotomy for coronary artery bypass grafting on the beating heart, with low early complications and good mid and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…MICS CABG has been proven to be a reliable and reproducible alternative to conventional CABG 6 . Convincing data show that MICS CABG provides the benefits of a low transfusion rate, short length of hospital stay, and rapid recovery to normal activity 7,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MICS CABG has been proven to be a reliable and reproducible alternative to conventional CABG 6 . Convincing data show that MICS CABG provides the benefits of a low transfusion rate, short length of hospital stay, and rapid recovery to normal activity 7,12 …”
Section: Discussionmentioning
confidence: 99%
“…In the era of minimally invasive surgery, patients prefer durable outcomes with less invasive approaches, which help them to recover their normal activity. Minimally invasive coronary surgery–CABG (MICS CABG) via left anterior thoracotomy is reportedly a less invasive and sternum‐sparing approach for multivessel or left main artery disease 6‐9 . Unlike CABG via a sternotomy, which has been studied for many years with convincing data showing its effectiveness and reproducibility, fewer objective data are available for MICS CABG, especially angiographic data regarding the graft patency and CR rates 10‐12 …”
Section: Introductionmentioning
confidence: 99%
“…This concept was then developed by Guida et al 8 who introduced a similar thoracotomy technique, named anterolateral thoracotomy coronary artery bypass (ALT‐CAB). Recently, these authors reported the 15‐year experience, including more than 2500 patients with excellent perioperative and long‐term results 9 . Later on, McGinn and Ruel 3 pioneered MICS CABG.…”
Section: Discussionmentioning
confidence: 99%
“…MICS CABG has been proven to be a reliable and reproducible alternative to conventional CABG 6 . Convincing data show that MICS CABG provides the benefits of a low transfusion rate, short length of hospital stay, and rapid recovery to normal activity 7,12 . Graft patency and CR are predictive of the short-and long-term outcomes of patients who undergo coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of minimally invasive surgery, patients prefer durable outcomes and less invasiveness, which help them to recover their normal activity. Minimally invasive coronary surgery-CABG (MICS CABG) via left anterior thoracotomy is reportedly a less invasive and sternum-sparing approach for multivessel or left main artery disease [6][7][8][9] . Unlike CABG via sternotomy, which has been studied for many years with convincing data showing its effectiveness and reproducibility, fewer objective data are available for MICS CABG, especially angiographic data regarding the graft patency and CR rates [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%